Pembelajaran Daring dengan Menggunakan Platform Edlink: Sebagai Salah Satu Alternatif Pembelajaran di Masa Pendemi Covid-19 - Darwanto Darwanto; Mar'atun Khasanah (Eksponen, 2021)
Learning during the Covid-19 pandemic was carried out using distance learning. Distance learning can be done in two ways, namely offline learning and online learning. The Sevima Edlink application is a Management Learning System (MLS) that can be used and recommended in online learning